2022
DOI: 10.3390/ijms232112779
|View full text |Cite
|
Sign up to set email alerts
|

A Pyrazolate Osmium(VI) Nitride Exhibits Anticancer Activity through Modulating Protein Homeostasis in HepG2 Cells

Abstract: Interest in the third-row transition metal osmium and its compounds as potential anticancer agents has grown in recent years. Here, we synthesized the osmium(VI) nitrido complex Na[OsVI(N)(tpm)2] (tpm = [5-(Thien-2-yl)-1H-pyrazol-3-yl]methanol), which exhibited a greater inhibitory effect on the cell viabilities of the cervical, ovarian, and breast cancer cell lines compared with cisplatin. Proteomics analysis revealed that Na[OsVI(N)(tpm)2] modulates the expression of protein-transportation-associated, DNA-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…SOD2 promotes the effects of ROS, which in turn affects a cell's lifespan. Other study have shown that a Pyrazolate Osmium(VI) Nitride induces apoptosis through promoting HepG2 cells to release ROS [22]. These proteins are also the chemotherapeutic targets of cephalosporin antibiotics against cancers [23].…”
Section: Effects Of C24h20n2o7 On the Body Weight And Major Organ Coe...mentioning
confidence: 98%
“…SOD2 promotes the effects of ROS, which in turn affects a cell's lifespan. Other study have shown that a Pyrazolate Osmium(VI) Nitride induces apoptosis through promoting HepG2 cells to release ROS [22]. These proteins are also the chemotherapeutic targets of cephalosporin antibiotics against cancers [23].…”
Section: Effects Of C24h20n2o7 On the Body Weight And Major Organ Coe...mentioning
confidence: 98%